Breakfast consumption and associated factors and barriers among school-aged children - Aneley, Zelalem; Assaye, Hirut; Mekonen, Habitamu; Bewket, Yenewa; Lake, Embet; Fentahun, Andualem (Frontiers in Nutrition, 2024)
Background: Breakfast provides the energy and nutrition we need to function at best, both mentally and physically. It is also plausible to propose that children's general development is impacted when they skip breakfast.Objective: To assess the prevalence of breakfast consumption and associated factors and predictors among public primary school children in Debremarkos Town, northwestern Ethiopia, 2022. Method: A community-based cross-sectional study was conducted among school-aged children in Debremarkos, Northwest Ethiopia. A multistage random sampling technique was used to select 609 study participants. The children's parents were interviewed using a pretested, structured questionnaire. For the rest of the analysis, SPSS version 20 was used. Logistic regression analysis was performed to assess the factors associated with breakfast consumption. Statistical significance was determined at a p value <0.05. Results: Out of the sampled children, 600 respondents participated in the study, for a response rate of 98.5%. The prevalence of regular breakfast consumption among school-aged children was 67.5%. Higher odds of regular breakfast consumption were found among respondents who were females (AOR = 1.72, 95% CI = 0.118-1.773), those who lived in high-income families (AOR = 7.33, 95% CI = 1.036-8.110), and those who had an educated family (AOR = 13.05, 95% CI = 0.019-13.1). However, lower odds of regular breakfast intake were found among respondents aged 9-12 years (AOR = 0.54, 95% CI = 0.369-0.79). Breakfast is a major health concern for school-aged children in Debremarkos city. Breakfast eating is associated with several factors; the most notable factor is being female, having a high income, and having an uneducated family. Therefore, to prevent children from skipping breakfast, stakeholders must move swiftly.